"Doing school" : how we are creating a generation of stressed out, materialistic, and miseducated students - Pope, Denise Clark, 1966- (New Haven, CT : Yale University Press, 2001)
Denise Pope, veteran teacher and curriculum expert, follows five motivated and successful students through a school year, closely shadowing them and engaging them in lengthy reflections on their school experiences. What emerges is a double-sided picture of school success. On the one hand, these students work hard in school, participate in extracurricular activities, serve their communities, earn awards and honors, and appear to uphold school values. But on the other hand, they feel that in order to get ahead they must compromise their values and manipulate the system by scheming, lying, and cheating. In short, they "do school"--That is, they are not really engaged with learning nor can they commit to such values as integrity and community. The words and actions of these five students-- two boys and three girls from diverse ethnic and socioeconomic backgrounds-- underscore the frustrations of being caught in a "grade trap" that pins future success to high grades and test scores. Their stories raise critical questions that are too important for parents, educators, and community leaders to ignore. Are schools cultivating an environment that promotes intellectual curiosity, cooperation, and integrity? Or are they fostering anxiety, deception, and hostility? Do today's schools inadvertently impede the very values they claim to embrace? Is the "success" that current assessment practices measure the kind of success we want for our children?
Welcome to Faircrest High -- Kevin Romoni: a 3.8 kind of guy -- Eve Lin: life as a high school machine -- Teresa Gomez: "I want a future" -- Michelle Spence: keeping curiosity alive? -- Roberto Morales: when values stand in the way -- The predicament of "doing school" -- Epilogue -- Appendixes. A. General information about the students in the study ; B. Common student behavior exhibited in pursuit of success.
Includes bibliographical references (pages 207-212).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Academic achievement -- United States; High school students -- United States; Student aspirations -- United States; Élèves du secondaire -- États-Unis.; Succès scolaire -- États-Unis.; Élèves -- Aspirations -- États-Unis.; EDUCATION -- Secondary; EDUCATION -- Student Life & Student Affairs; Academic achievement; High school students; Student aspirations; United States; High school; Schüler; USA; Computer network resources